Tungsten Increases Sex-Specific Osteoclast Differentiation in Murine Bone. (21st November 2020) - Chou, Hsiang; Grant, Michael P; Bolt, Alicia M; Guilbert, Cynthia; Plourde, Dany; Mwale, Fackson; Mann, Koren K
Abstract: Tungsten is a naturally occurring metal that is increasingly used in industry and medical devices, and is labeled as an emerging environmental contaminant. Like many metals, tungsten accumulates in bone. Our previous data indicate that tungsten decreases differentiation of osteoblasts, bone-forming cells. Herein, we explored the impact of tungsten on osteoclast differentiation, which function in bone resorption. We observed significantly elevated osteoclast numbers in the trabecular bone of femurs following oral exposure to tungsten in male, but not female mice. In order to explore the mechanism(s) by which tungsten increases osteoclast number, we utilized in vitro murine primary and cell line pre-osteoclast models. Although tungsten did not alter the adhesion of osteoclasts to the extracellular matrix protein, vitronectin, we did observe that tungsten enhanced RANKL-induced differentiation into tartrate-resistant acid phosphatase (TRAP)-positive mononucleated osteoclasts. Importantly, tungsten alone had no effect on differentiation or on the number of multinucleated TRAP-positive osteoclasts. Enhanced RANKL-induced differentiation correlated with increased gene expression of differentiated osteoclast markers Nfatc1, Acp5, and Ctsk . Although tungsten did not alter the RANK surface receptor expression, it did modulate its downstream signaling. Co-exposure of tungsten and RANKL resulted in sustained positive p38 signaling. These findings demonstrate that tungsten enhances sex-specific osteoclast differentiation, and together with previous findings of decreased osteoblastogenesis, implicate tungsten as a modulator of bone homeostasis.